The Role of Artificial Intelligence in Improving the Product Life Cycle - Sally Ibrahim Ahmed (International Journal of Innovative and Applied Finance, 2025)
Recent advances in artificial intelligence (AI) in general, and its components of digital transformation, deep learning, expert systems, and innovation in particular, are enabling tremendous impact on society and industries. However, the use and impact of AI for production purposes remains limited. This research aims to identify the impact of AI on improving product lifecycles. Data was collected from a sample of specialized experts. The research adopted a descriptive and analytical approach using correlation analysis, regression, and structural modeling tools. The research reached a set of conclusions, the most important of which are: AI positively transforms production methods by analyzing complex data, market trends, and operational performance beyond the capabilities of workers.